‘Echoes From Africa’: Abdullah Ibrahim’s Black Sonic Geography - Ramphalile, Molemo; Manyike, Thabang; Maxaulane, Gregory (Kronos: Southern African Histories, 2024)
This article aims to listen, read and move with the South African musician Abdullah Ibrahim by focusing on various works in his corpus that see him weave together a sonic aesthetic and identify sound, space and time as fundamentally intertwined with and constituted by the experiences of racial violence and anti-blackness in a modern colonial world. Part of our critical pursuit is to highlight Abdullah Ibrahim as a theorist of black geography invested in the everyday sounds ringing through the ghettoes, townships and reserves created as debased and inexhaustible reservoirs for cheap labour by colonial-apartheid regimes. We will also examine how some of Abdullah Ibrahim’s music interrogates the status of the black subject through the modalities of a black Islamic sonic aesthetic. This is one of the factors which qualifies it as a layered site of mythical and experimental histories and enables us to identify his body of work as deeply connected with the articulations of loss, suffering, the cadence of change, and hope.